Global tour : Art, travel & beyond : an exhibition based on research and a concept by Amiel Grunberg (1980-2004). - Augé, Marc; Azizov, Zeigam; Cleary, Anne; Demeester, Ann; Drabble, Barnaby; Grumberg, Amiel; Guerreiro, Nelson; Jeanpierre, Laurent; Lamm, Olivier; Mateo, Ferran; Perillat, Laurence; Pinto, Roberto; et al. (Amsterdam : W 139 Amsterdam, 2005)
Achour, Boris ; Auguste-Dormeuil, Renaud ; Azizov, Zeigam ; Balula, Davide ; Baraya, Alberto ; Berchem, Otto ; Bernado, Jordi ; Breitz, Candice ; Cantor, Mircea ; Castro, Jota ; Cleary, Anne ; Connolly, Denis ; Fusco, Coco ; Gaba, Meschac ; Garaicoa, Carlos ; Hong Hao ; Krenn, Martin ; Perjovschi, Dan ; Ressler, Oliver ; Roush, Paula ; Spalinger, Nika ; Sriwanichpoom, Manit
biog., ind.tent., gr. tent. p. 154-165
Engels
boek